Phythotechnology of Touch Industrial Waste Treatment in Sidoarjo using Typha Latifolia Plant to Reduce TDS and Ammonia Levels - Oktavia, Lily; Taufiq, Mohammad; Tamyiz, Muchammad (Journal of Research and Technology, 2021)
Sidoarjo Regency is a buffer zone for industrial estates in Surabaya, East Java Province. Therefore, the economic growth of the Sidoarjo Regency is increasing along with the development of trade and industrial potential. One of the industries that have grown well in Sidoarjo Regency is the tofu factory. Many tofu craftsmen industry causes an increase in the volume of liquid waste which also flows into water bodies. The purpose of this study was to determine the reduction of TDS and ammonia levels in the tofu factory wastewater treatment in the Sepande area, Sidoarjo Regency, by using a wetland construction with a Typha latifolia remediator. The research stages will be carried out using a laboratory scale using acclimatization as the adaptation stage of Typha latifolia and a constructed wetland reactor as a phytoremediation process. Based on the results and discussion, it can be concluded that there was a decrease in TDS and ammonia levels in the tofu industrial wastewater in Sidoarjo with the Constructed Wetland system. The largest decline in TDS content was in soil media with three Typha latifolia stems and a detention time of four days by 76%. Meanwhile, the most considerable percentage reduction in ammonia levels occurred in sand media with three stems of Typha latifolia and a detention time of four days by 70%.